Sintesis dan Karakterisasi Komposisi Unsur, Oksida dan Stabilitas Termal Katalis Berbasis CaO, MgO dan SiO2 - Kasimir Sarifudin; Sri Adeningsi Petroni Henukh (Media Sains, 2025)
Characterizing the elemental constitution, composition of oxides, and thermal stability of CaO/SiO₂, MgO/SiO₂, and CaO-MgO/SiO₂ catalysts has been the subject of this research. The sol-gel process was used to convert natural zeolite into silica. We used HCl in order for the silica to settle out after dissolving it in NaOH from the zeolite framework. Hard water deposits were transformed into CaO through the sol-gel process. HCl was utilized during the hydrolysis procedure, and Na₂CO₃ was employed during the condensation stage. The mixture was then calcined and dried. When heated, the precursor MgCO₃ breaks down into MgO. CaO and MgO are dispersed using the wet impregnation process onto the SiO₂ support's surface. XRF equipment was used to characterize each material's elemental and oxide composition. TGA was used to examine each catalyst's thermal stability. According to the elemental and oxide composition characterization results, each material had more than 90% major elements and oxides and less than 1% impurities. SiO₂ lost 4% of its weight during the thermal stability test, which was conducted between 30 and 800°C at a rate of 10°C/minute. The weight loss for MgO/SiO₂, CaO, CaO-MgO/SiO₂, and CaO/SiO₂ was 12.5%, 18.14%, 25.27%, and 27.82%, respectively. According to each material's mass loss, SiO₂ > MgO/SiO₂ > CaO > CaO-MgO/SiO₂ > CaO/SiO₂ was the order of thermal stability from most stable to least stable.